Latha Menon (Executive Editor). Microsoft Encarta Encyclopedia Deluxe 2000 - Louw, Phillip (Lexikos, 2000)
In the highly competitive world of CD-ROM encyclopaedias, Microsoft hasconsistently outperformed its competitors with products for the whole family.Microsoft Encarta Encyclopedia Deluxe 2000 (henceforth Encarta 2000) is the latestflagship of this line of products. The millennium edition is said to be "a modernreference resource that provides a richness of learning experience for people ofall ages that extends far beyond what was possible with traditional referenceworks" (Letter from the editor). This claim reflects the feature which sets CDROMencyclopaedias apart from their printed equivalents - their accessibility.The executive editor emphasizes accessibility as one of the central values of theeditorial staff of Encarta 2000.